Pokušaj periodizacije djelatnosti Adolfa Bratoljuba Klaića - Samardžija, Marko, lingvist (Array, 2014)
The Croatian linguist, lexicographer and translator Adolf Bratoljub Klaić (born in Bizovac in 1909 - died in Zagreb in 1983) published his first literary work in the journal "Youth" ("Omladina") in 1926 (the poem "Na grobu srpanjskih žrtava"/"On the grave of the victims of July"). The author proposes a periodization of the total work of A. B. Klaić from 1926 to his death. The first period (from 1926 to 1932) includes his early literary works, his cooperation in the journal "Hrvat" ("The Croat") and the first article about the Croatian dialect in Slavonia in the Middle Ages. In the second period (from about 1932 to 1941) he worked as a secondary school teacher and went abroad 3 times (once to Prague and twice to Poland). On 7th February 1941 he got his doctor's degree at the University of Zagreb (thesis "Bizovačko narječje"/"The Dialect from Bizovac"). In the third period (April 1941-May 1945) A. B. Klaić was an associate of the Croatian State Office for the language (from 1942 The Office for Croatian language). He arranged the books Koriensko pisanje (in 1942) and Hrvatski pravopis (in 1944) in the accordance with the ethymological orthography concept. The fourth period lasted from 1945 until the late fifties. In this period he wrote about Croatian orthography issues, started translating from Latin and edited the Croatian accents in the entries of two very important bilingual dictionaries. The fifth period includes Klaić's works since the early 1960's. He contributed to the edition "Pet stoljeća hrvatske književnosti" ("Five Centuries of Croatian Literature") and translated from Latin and Greek (Sophocles, Euripides, Aeschylus, Virgil, Plato). He published the book Izmedu jezikoslovlja i nauke o književnosti ("Between Linguistics and the Science of Literature"; 1972). Klaić's literary works which he had published all his life and his work Rječnik stranih riječi ("The Dictionary of Foreign Words") were not included in the proposed periodiza